2022
DOI: 10.3389/fpls.2022.828467
|View full text |Cite
|
Sign up to set email alerts
|

Comparative and Phylogenetic Analysis Based on the Chloroplast Genome of Coleanthus subtilis (Tratt.) Seidel, a Protected Rare Species of Monotypic Genus

Abstract: Coleanthus subtilis (Tratt.) Seidel (Poaceae) is an ephemeral grass from the monotypic genus Coleanthus Seidl, which grows on wet muddy areas such as fishponds or reservoirs. As a rare species with strict habitat requirements, it is protected at international and national levels. In this study, we sequenced its whole chloroplast genome for the first time using the next-generation sequencing (NGS) technology on the Illumina platform, and performed a comparative and phylogenetic analysis with the related species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 103 publications
6
10
0
Order By: Relevance
“…The GC content was identical to the other Rubiaceae family members [ 26 , 44 , 45 ]. The IR areas contained four rRNA genes with high GC content, which supported the hypothesis of previous research [ 46 , 47 , 48 , 49 ]. A previous study found that the GC content was substantially higher, most likely due to the abundance of rRNA in the IR regions [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The GC content was identical to the other Rubiaceae family members [ 26 , 44 , 45 ]. The IR areas contained four rRNA genes with high GC content, which supported the hypothesis of previous research [ 46 , 47 , 48 , 49 ]. A previous study found that the GC content was substantially higher, most likely due to the abundance of rRNA in the IR regions [ 50 ].…”
Section: Discussionsupporting
confidence: 89%
“…During the evolution of terrestrial plants, the chloroplast genome’s IR region frequently experiences length variations, which results in the formation of a variety of boundary features [ 32 , 49 , 53 ]. Furthermore, the primary causes of the size change in cp genomes are the contraction and expansion of IR regions and the single-copy (SC) border regions, which influences the cp genome’s rate of evolution [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Twenty-two intron-containing genes out of 125 genes were detected in these CP genomes. Among them, the trnK-UUU gene embodied the matK genes and had the largest intron (over 2,500 bp), which has been reported in previous studies (Li X. et al, 2019;Souza et al, 2020;Ren et al, 2022). matK is a well-known gene that is often used for molecular identification and analysis of genetic relationships in plants (Hilu and Liang, 1997;Ramesh et al, 2022), including Morus (Venkateswarlu et al, 2012).…”
Section: Morus Cp Genome Characterizationmentioning
confidence: 82%